Fluid flow modeling of a four-stage damping adjustable shock absorber and its experimental research. Issue 1 (5th February 2018) - Ding, Erming; Xie, Fangwei; Dai, Heng; Gao, Qingsong; Zhang, Jin; Feng, Yixiang; Liu, Hongtuo
Abstract : Purpose: In order to improve the ride comfort of vehicle suspension, this paper first proposed a shock absorber with four-stage adjustable damping forces. The purpose of this paper is to validate its modeling and characteristics, indicator diagrams and velocity diagrams, which are the main research points. Design/methodology/approach: In order to validate the fluid flow modeling, a series of mathematical modeling is established and solved by using Matlab/Simulink. An experiment rig based on electro-hydraulic loading servo system is designed to test the prototype. Finally, indicator diagram and velocity diagram are obtained and compared both in simulation and experiments. Findings: Results indicate that at the same damping position, damping force will increase with the rise of rod's velocity: if the rod's velocity is fixed, the damping force changes apparently by altering the damping position. The shock absorber is softest at damping position 1, and it is hardest at damping position 4; although there is no any badly empty stroke and skewness in indicator diagram by simulation, a temporary empty stroke happens at maximum displacement of piston rob, both in rebound and compression strokes. Research limitations/implications: Compared with results of the simulation and experiments, the design of a four-stage damping adjustable shock absorber (FDASA) is validated correctly in application, and may improve the overall dynamic performance of vehicle. Originality/value: This paper is mainly focused on the design and testing of an FDASA, which may obtain four-stages damping characteristics, that totally has a vital importance to improve the performance of vehicle suspension.